The knights of Crystallia - Sanderson, Brandon; Lazo, Hayley (New York : Starscape, a Tom Doherty Associates Book, 2016)
The Knights of Crystallia have taken away Bastille's sword and armor. Alcatraz, Bastille and their wacky relatives must figure out what's going on in order to save the Free Kingdoms from doom.
Ages 9-13.
104873
Keywords: Librarians -- Juvenile fiction; Grandfathers -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy fiction